Efeitos do exercício físico sobre distúrbios neuropsiquiátricos e atividades instrumentais da vida diária em mulheres com doença de Alzheimer: Um ensaio clínico controlado - Nascimento, Carla Manuela Crispim [UNESP]; Teixeira, Camila V.L. [UNESP]; Gobbi, Lilian T.B. [UNESP]; Gobbi, Sebastião [UNESP]; Stella, Florindo [UNESP] (FapUNIFESP (SciELO), 2012)
Objective: To analyze the influence of a six-month exercise program on neuropsychiatric disorders and on the performance of instrumental activities in elderly patients with Alzheimer's disease (AD). Methods: The study included 20 patients with AD in the mild to moderate stages of the Clinical Dementia Rating (CDR) divided into two groups: the experimental group, composed of 10 women who participated in the six-month exercise program, and the control group, composed of the 10 remaining AD patients who did not take part in an exercise program during the same period. All participants were evaluated using the Mini-Mental State Exam for global cognitive function, the Neuropsychiatric Inventory Questionnaire for neuropsychiatric disorders, and the Pfeffer Functional Activities Questionnaire for the degree of functional impairment. Results: The control group showed functional and neuropsychiatric deterioration in the comparisons between pre- and post-intervention times and between groups. Conclusion: The experimental group showed a propensity for less deterioration in neuropsychiatric disorders and performance of instrumental activities compared to the sedentary group. Trial registration RBR-4qzm6s.
A controlled clinical trial on the effects of exercise on neuropsychiatric disorders and instrumental activities in women with Alzheimer's disease
Keywords: Alzheimer's disease; Dementia; Instrumental activities; Neuropsychiatric disorders; Physical exercise; Physical therapy